Criteria and indicators of the effectiveness of the methodological system of fundamentalized training of future specialists in the field of information technologies - Bardus, I. (Problems of Engineer-Pedagogical Education, 2018)
The article develops a system of criteria and indicators of the effectiveness of the methodological system of fundamentalized vocational training of future specialists in the field of information technologies for productive vocational activities. The author has determined that the main criteria of the effectiveness of the methodological system are the criteria for measuring the formation of organizational, technological and managerial competences of an IT specialist. The criteria for measuring the formation of organizational competence are the criteria for assessing the formation of the relevant competences, namely competences related to technical preparation, ensuring the functioning and control over the process of manufacturing an IT product. The criteria for the formation of technological vocational competence are the criteria for the formation of such competences as: designing, manufacturing, operating, improving and repairing of the IT product. Criteria for the formation of administrative competence of an IT specialist are criteria for the formation of competences related to resource planning, accounting and analysis, and regulation of the IT production process. The author has singled out the groups of indices which indicate the level of the acquisition of relevant knowledge, skills and abilities to perform organizational, technological and managerial productive activities and groups of indicators of the formation of professionally important personal qualities of an IT specialist. The groups of indicators of the formation of professionally important qualities should consist of the groups of indicators of the formation of cognitive, motivational and target-oriented, organizational and activity-oriented characteristics of the individual.